2018
DOI: 10.3390/rs10091485
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Estimating Beneficial Arthropod Populations: Implications of a Low-Cost Small Unmanned Aerial System

Abstract: Studies show that agricultural land requires investment in the habitat management of non-cropped areas to support healthy beneficial arthropods and the ecosystem services they provide. In a previous small plot study, we manually counted blooms over the season, and found that plots providing greater numbers of flowers supported significantly higher pollinator populations over that of spontaneous weed plots. Here, we examined the potential of deploying an inexpensive small unmanned aerial vehicle (UAV) as a tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Drones may be useful for capturing floral data relevant to pollination research as they can be operated over spatial areas that roughly match the distances covered by many foraging pollinators (Osborne et al, 2008;Danner et al, 2016), with maximum operating distances of up to 10 km, depending on the aircraft model, and limited by legislative restrictions (Duffy et al, 2018). Their proximity to the Earth's • Developed by Sun et al, 2021 surface means that the grain of such observations has capacity to capture flower-scale information (e.g., Wan et al, 2018;Xavier et al, 2018;Chen et al, 2019;López-Granados et al, 2019). Furthermore, drones with high-quality inbuilt cameras are becoming more affordable (£500-£2000) for the everyday field ecologist, and there is the possibility to further modify these with customized sensors.…”
Section: Structure From Motion (Sfm) Photogrammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Drones may be useful for capturing floral data relevant to pollination research as they can be operated over spatial areas that roughly match the distances covered by many foraging pollinators (Osborne et al, 2008;Danner et al, 2016), with maximum operating distances of up to 10 km, depending on the aircraft model, and limited by legislative restrictions (Duffy et al, 2018). Their proximity to the Earth's • Developed by Sun et al, 2021 surface means that the grain of such observations has capacity to capture flower-scale information (e.g., Wan et al, 2018;Xavier et al, 2018;Chen et al, 2019;López-Granados et al, 2019). Furthermore, drones with high-quality inbuilt cameras are becoming more affordable (£500-£2000) for the everyday field ecologist, and there is the possibility to further modify these with customized sensors.…”
Section: Structure From Motion (Sfm) Photogrammetrymentioning
confidence: 99%
“…Fine-grain data acquired by drones could also be important to studying the efficacy of alternative agricultural practices, such as those seeking to enhance crop yields by providing a mix of diverse floral resources to attract pollinators. These studies could be carried out using relatively simple-touse and cheap consumer-grade technologies as evidenced by Xavier et al (2018), who used a drone (Solo-3DR) and GoPro Hero 4 RGB camera (12-megapixel photos) to capture spatial data on floral resources. The study assessed the suitability of wildflower strips in attracting pollinators in two distinct types of environments: one in which the wildflower strips were adjacent to woodland, and another in which the wildflower strips were adjacent to agricultural crops.…”
Section: How Isolated Are Floral Resources?mentioning
confidence: 99%
“…Only recently, some efforts and successful attempts to bring UAS technologies within an agroecological framework to manage agricultural lands and agroforest ecosystems were accomplished (Xavier et al, 2018;Padua et al, 2017;Libràn-Embid et al, 2020). The role of integrating biodiversity conservation with habitat management for agricultural-landscape diversification is widely documented.…”
Section: Agroecosystems and Biodiversity Monitoringmentioning
confidence: 99%
“…Unmanned aerial vehicles (UAV) borne with sensors along with image processing tools aid in identification and classification of floral resources to predict the occurrence and abundance of pollinators (Lino et al, 2011). Xavier et al 2018 reported that an UAV equipped with digital camera to capture the images of the floral area and the captures images were subjected supervised image classification to study the correlation between the floral counts and pollinator abundance. High spatial and temporal data especially Photosynthetic active radiation (PAR) and Leaf Area Index (LAR), greening and browning of vegetation will directly help to assess the preference of bees for foraging in an agricultural landscape (Nightingale et al, 2008).…”
Section: Unmanned Aerial Vehicles In Mapping Floral Areasmentioning
confidence: 99%